Mindfulness-based cognitive therapy: further issues in current evidence and future research. - Williams, J; Russell, I; Russell, D (2008)
The authors respond to the article by H. F. Coelho, P. H. Canter, and E. Ernst (2007), which reviewed the current status of mindfulness-based cognitive therapy (MBCT). First, they clarify the randomization procedures in the 2 main MBCT trials. Second, they report posttreatment and follow-up data to show that trial participants allocated to "treatment as usual" did not become worse. Third, they discuss which experimental designs are better for identification of the active component of treatment. Finally, they report reanalyses of the 2 main MBCT trials with multilevel modeling that corrected for intragroup correlations. These analyses reinforce the original findings: For patients with 3 or more previous episodes, MBCT significantly reduced the risk of a further episode of depression and significantly decreased mean scores on the Beck Depression Inventory (A. T. Beck, C. H. Ward, M. Mendelson, J. Mock, and J. Erbaugh, 1961) after treatment.